Pelatihan Penyusunan Laporan Keuangan Sederhana Bagi Pelaku UMKM Di Desa Tegalarum Kecamatan Mranggen Kabupaten Demak - Saifudin Saifudin; Aprih Santoso; Sri Yuni Widowati (IAI Darussalam, 2021)
In order to increase the opportunities, capabilities and protection of SME actors, various policies have been established on the empowerment of SMEs which are carried out by fostering a business climate that supports the development of Micro, Small and Medium Enterprises and Development and fostering of Micro, Small and Medium Enterprises, Problems. what MSMEs players face in Tegalarum Village, Mranggen District, Demak Regency, are: (1) lack of knowledge about the preparation of financial reports. (2) There is no facility in the form of a training program that has been used yet. (3) There is no assistance for the preparation of financial reports. The purpose of PKM is to provide training to MSME players in Tegalarum Village, Mranggen District, Demak Regency so that they can find out about business developments and use financial reports to support the progress of their MSMEs. The results of PKM are the ability and skills to prepare financial reports by MSMEs actors in Tegalarum Village, Mranggen District, Demak Regency. The recommendation for the results of the implementation of PKM is to remember that compiling this financial report is a work that is continuous and sustainable, so it is better if the MSME actors in Tegalarum Village, Mranggen District, Demak Regency, do it regularly every time there is a transaction.